Frequency of hand contact with hospital surfaces in hospitalized pediatric patients - José F. Mier-de Leija; Daniela de la Rosa-Zamboni; Juan J. L. Sienra-Monge; Horacio Márquez-González; Solange G. Koretzky (Permanyer, 2024)
Background: Hand hygiene (HH) is an important strategy for preventing health-care-associated infections (HAIs). Few programs focus on HH for family members and primary caregivers but fewer for patients. This study aimed to estimate the frequency with which hospitalized pediatric patients have hand contact with hospital surfaces. Methods: We conducted a cross-sectional descriptive observational study consisting of three phases: the first was the creation of an observation and data collection tool, the second was the training of the monitors, and the third was the observational study of hand contact and HH opportunities in hospitalized pediatric patients. Results: Over 3600 minutes of observation, 2032 HH opportunities were detected, averaging 33.8/h (SD 4.7) as determined by hand contact with hospital surfaces of hospitalized pediatric patients. In our study, infants and preschool children had the highest frequency of hand contact. Conclusion: The high frequency of hand contact of hospital surfaces by children suggests that hourly hand disinfection of patients and caregivers, objects and surfaces around the patients may be prevention measures that could be incorporated to reduce HAIs in pediatric hospitals.